Hierarchical porous CeO2 micro rice-supported Ni foam binder-free electrode and its enhanced pseudocapacitor performance by a redox additive electrolyte. (6th July 2021) - Arunpandiyan, S.; Raja, A.; Vinoth, S.; Pandikumar, A.; Arivarasan, A.
Abstract : A hierarchical porous CeO2 micro rice/NF binder free electrode was fabricated via a facile hydrothermal method and the electrochemical performances were enhanced by the addition of 0.2 M K4 [Fe(CN)6 ] redox additive in a 3 M KOH electrolyte. Abstract : Developing high-performance, robust and economic supercapacitors is a promising path to the future electric vehicle technology. Herein, a hierarchically porous CeO2 micro rice was attached onto a Ni foam (NF) surface via a facile hydrothermal approach. The fabricated binder-free electrode exhibited a maximum specific capacitance of 728.3 F g −1 in a 3 M KOH electrolyte. Further, this value was improved to 2319.5 F g −1 by the 3 M KOH + 0.2 M K4 [Fe(CN)6 ] redox additive electrolyte. The improved electrochemical performance was achieved by reversible redox reactions that occurred in the electrolyte due to the inclusion of 0.2 M K4 [Fe(CN)6 ]. The as-prepared binder-free electrode has retained 85.3% of its initial capacitance in 3 M KOH, even after 5000 cycles, and in the redox additive electrolyte, the retention increased to 92.7%. The highest energy and power density of 39.6 W h kg −1 and 550 W kg −1, respectively, were achieved in the redox additive electrolyte.